Extraosseous Plasmacytoma of Thyroid Arising in Hashimoto’s Thyroiditis - Matthew Crabtree; Ping Ji; Jennifer Cindy Cai; Xin Qing (Journal of Hematology and Oncology Research, 2020)
Plasma cell neoplasms of the thyroid gland are uncommon. They may occur either as a primary extraosseous (extramedullary) plasmacytoma or as secondary involvement by multiple myeloma (MM). Here, we report the case of a 62-year-old female, presenting with goiter and Hashimoto’s thyroiditis, in whom the histologic diagnosis of extraosseous plasmacytoma was unexpected. Histology of the total thyroidectomy specimen showed a diffuse infiltration of well-differentiated plasma cells against a background of Hashimoto’s thyroiditis. By immunohistochemistry, the majority of the plasma cells are positive for IgG heavy chain and kappa light chain (kappa:lambda ratio was about 6-7:1). PCR analysis of the immunoglobulin heavy and kappa chain (IGH, IGK) gene rearrangements showed clonal IGH and IGK gene rearrangements. MM was ruled out by lack of MM-related end organ damage and negative serum protein electrophoresis, immunofixation, and bone marrow biopsy. Although rare, plasmacytoma should be considered in patients presenting with enlarging thyroid gland and autoimmune thyroiditis. Histologic diagnosis and differential diagnoses are comprehensively discussed.
Keywords: plasmacytoma